2013
DOI: 10.1002/masy.201300005
|View full text |Cite
|
Sign up to set email alerts
|

Preparative TREFHTHPLCHPer DSC: Linking Molecular Characteristics and Thermal Properties of an Impact Poly(propylene) Copolymer

Abstract: Summary:The microstructure and thermal behaviour of complex polyolefins affect the product properties significantly. Therefore a thorough characterization of such semi-crystalline materials is necessary to understand the relationship between molecular structure and melting and crystallization behaviour. In the present work, the correlation between the chain structure and thermal behaviour of various components in a complex midelution temperature TREF fraction (80 C) of a commercial impact poly(propylene) copol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…DSC is a simple and widely used method, however, the crystallization behavior is strongly influenced by the thermal history of the sample . Solution crystallization‐based techniques, such as temperature rising elution fractionation (TREF) and crystallization analysis fractionation (CRYSTAF), have been utilized to analyze CCD of EPR copolymers with high ethylene contents. It has been indicated by both techniques that these copolymers are completely amorphous or contain only very small amounts of crystallizing material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DSC is a simple and widely used method, however, the crystallization behavior is strongly influenced by the thermal history of the sample . Solution crystallization‐based techniques, such as temperature rising elution fractionation (TREF) and crystallization analysis fractionation (CRYSTAF), have been utilized to analyze CCD of EPR copolymers with high ethylene contents. It has been indicated by both techniques that these copolymers are completely amorphous or contain only very small amounts of crystallizing material.…”
Section: Introductionmentioning
confidence: 99%
“…The recently developed high temperature–high performance liquid chromatography (HT‐HPLC) allows the analysis of both the amorphous and the crystalline fractions since the separation depends on the interaction or adsorption of the macromolecules with the stationary phase . For EPR copolymers it had been reported that on a graphitic stationary phase the separation depends mainly on the ethylene content of the sample . The HPLC chromatograms of EPR copolymers with high ethylene contents had shown multimodal elution profiles that indicate the complexity of these samples .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, by using a combination of LCCC and pure desorption promoting solvent both constituents of hiPP could be baseline separated and detected. In difference to the previously described HPLC systems for the separation of hiPP, which required gradient elution (1‐decanol→TCB or n‐decane → TCB, the HPLC system described here uses two eluents (2‐octanol/ODCB and ODCB) at constant composition.…”
Section: Resultsmentioning
confidence: 99%